1994
DOI: 10.1111/j.1365-2141.1994.tb05017.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐alpha up‐regulates bcl‐2 expression and protects B‐CLL cells from apoptosis in vitro and in vivo

Abstract: The bcl-2 oncoprotein, which is involved in the t(14,18) translocation, protects cells against apoptosis. We examined the effects of interferon-alpha (IFN-alpha) on bcl-2 protein expression and apoptosis in B-chronic lymphocytic leukaemia (B-CLL) cells. None of 12 patients with B-CLL examined expressed the t(14,18) translocation; however, all these, and seven other patients, expressed significant levels of bcl-2 protein. In vitro, IFN-alpha (500 U/ml over 18 h) increased bcl-2 expression on CLL cells (to 200 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 33 publications
2
65
0
Order By: Relevance
“…56 Yet other nets involved in Type-I-IFN-induced cell-cycle arrest are believed to include the downregulation of the transcription factor MYC and the activation of mitogen-activated protein kinase (MAPK)14 or the adapter molecule CRK. 57,58 Contrasting experimental findings indicate that Type-I-IFNs can either induce tumor cell death 59 or protect cancer cells from chemical-induced apoptosis 60 (panels 2 and 5, Fig. 2).…”
Section: Cancer-intrinsic Effects Of Type-i-ifnsmentioning
confidence: 80%
“…56 Yet other nets involved in Type-I-IFN-induced cell-cycle arrest are believed to include the downregulation of the transcription factor MYC and the activation of mitogen-activated protein kinase (MAPK)14 or the adapter molecule CRK. 57,58 Contrasting experimental findings indicate that Type-I-IFNs can either induce tumor cell death 59 or protect cancer cells from chemical-induced apoptosis 60 (panels 2 and 5, Fig. 2).…”
Section: Cancer-intrinsic Effects Of Type-i-ifnsmentioning
confidence: 80%
“…STATs are central mediators of cytokine-induced transcriptional activation [42]. It has been shown that IFN-a/b induce, through activation of JAK family kinases, the tyrosine phosphorylation and nuclear translocation of STAT1 and STAT2 [24].…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][8][9][10][11][12][13][14][15] NGF is an autocrine survival factor for memory B cells. 41 We tested whether IL-2, IL-4, IL-6, IL-8, IFN-␣, IFN-␥, NGF or G-CSF would induce B-CLL cell NOS2 enzyme activity following in vitro culture.…”
Section: Cytokine Induction Of B-cll Cell Nos2 Enzyme Activity and Prmentioning
confidence: 99%
“…3 A variety of factors prevent spontaneous apoptosis of cultured B-CLL cells; these include IL-2, IL-4, IL-6, IL-8, IFN-␣, IFN-␥, G-CSF, CD40 ligation, CD6 ligation and bone marrowderived stromal cells. [4][5][6][7][8][9][10][11][12][13][14][15][16] The lipid-soluble, gaseous free radical nitric oxide (NO) is an important regulator of apoptosis, and the viability of cultured B-CLL cells is dependent on the autocrine production of NO. 17 B-CLL cell apoptosis is regulated by caspases that promote apoptosis and by factors such as bcl-2 which inhibit apoptosis.…”
Section: Introductionmentioning
confidence: 99%